Influence of choice of electrical stimulation site on peripheral neurophysiological and hypoalgesic effects. - Cheing GL; Chan WW (Journal of Rehabilitation Medicine (Medical Journals Sweden AB), 2009)
OBJECTIVE: To investigate whether the choice of electrode placement site in transcutaneous electrical nerve stimulation (TENS) over acupuncture points vs peripheral nerve points influences the peripheral neurophysiological effects as reflected in negative peak latency in the superficial radial nerve, and on sensory changes in terms of peripheral mechanical pain threshold and mechanical pain tolerance in humans. DESIGN: Randomized controlled trial. SUBJECTS: Forty-five healthy subjects by convenience sampling. METHODS: Subjects were randomly assigned to receive: (i) TENS with electrode placement on acupuncture points; (ii) TENS on non-acupuncture points along the same peripheral nerve; or (iii) no stimulation as the control. In the TENS groups, electrical stimulation was delivered at a frequency of 4 Hz and pulse duration of 200 mus for 30 min. RESULTS: Significant increases in negative peak latency and mechanical pain threshold over time (p = 0.015, 0.002) were found within the 2 active TENS groups. However, there was no significant difference between the 3 groups in all outcome measures at any of the measurement points (all p = 0.05). CONCLUSION: TENS over acupuncture points offers no additional hypoalgesic effects vs TENS over peripheral nerve points in a specific anatomical region.